2015
DOI: 10.1186/s13071-015-0820-7
|View full text |Cite
|
Sign up to set email alerts
|

Entamoeba histolytica: protein arginine transferase 1a methylates arginine residues and potentially modify the H4 histone

Abstract: BackgroundIn eukaryotes, histone arginine methylation associates with both active and repressed chromatin states depending on the residues involved and the status of methylation. Even when the amino-terminus of Entamoeba histolytica histones diverge from metazoan sequences, these regions contain arginine residues that are potential targets for methylation. However, histone arginine methylation as well as the activity of arginine methyltransferases (PRMTs) has not been studied in this parasite. The aim of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 44 publications
1
20
0
Order By: Relevance
“…Experimental evidence indicates that chromatin may also regulate gene expression in E. histolytica , as it has been demonstrated that E. histolytica DNA is organized into chromatin and that the nucleosome (the fundamental unit of chromatin) consists of four canonical histone dimers. In addition, E. histolytica produces proteins that acetylate, deacetylate and methylate histones [ 6 , 8 , 24 ], which are responsible for chromatin structure modifications. Post-translational modifications of histones and DNA methylation are two of the epigenetic mechanisms that have been best studied in eukaryotic organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental evidence indicates that chromatin may also regulate gene expression in E. histolytica , as it has been demonstrated that E. histolytica DNA is organized into chromatin and that the nucleosome (the fundamental unit of chromatin) consists of four canonical histone dimers. In addition, E. histolytica produces proteins that acetylate, deacetylate and methylate histones [ 6 , 8 , 24 ], which are responsible for chromatin structure modifications. Post-translational modifications of histones and DNA methylation are two of the epigenetic mechanisms that have been best studied in eukaryotic organisms.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, no PRMT substrates have been identified in Entamoeba spp., nor have any functional studies been performed. Recently, PRMT1a of E. histolytica was reported to be associated with gene expression regulation by dimethylation of H4R8 [ 27 ]. T. gondii CARM1 (PRMT homologue) resulted in decreased parasite viability due to the transient expression of enzymedead mutant TgCARM1 in tachyzoites [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…For western blot (WB) assays, membranes were stained with Ponceau S Red staining solution (Sigma-Aldrich) and incubated 1 h with 5% non-fat milk. Then were incubated overnight (ON) with α-TRF-like I (1:2,500), α-TRF-like III (1:1,000), α-EhKMT4 (1:1,000) (Borbolla-Vázquez et al, 2015 ); α-H3K27me3 (1:1,000, Cell Signaling Technology), α-H4K20me3 (1:1,000, Abcam), α-Lamin B1 (1:1,000, Abcam), α-actin (1:1,000, Sigma-Aldrich) or α-Myc (1:1,000, Cell Signaling Technology) antibodies and then, incubated for 2 h with the corresponding horseradish peroxidase (HRP) labeled secondary antibodies (1:8,000, Santa Cruz Biotechnology). Protein bands were detected and visualized by chemiluminescence on X-ray films.…”
Section: Methodsmentioning
confidence: 99%